Association of Hospital Safety Net Status With Outcomes and Resource Use for Extracorporeal Membrane Oxygenation in the United States. (April 2022) - Gandjian, Matthew; Williamson, Catherine; Xia, Yu; Maturana, Carlos; Chervu, Nikhil; Verma, Arjun; Tran, Zachary; Sanaiha, Yas; Benharash, Peyman
Purpose: Safety net hospitals (SNH) have been associated with inferior surgical outcomes and increased resource use. Utilization and outcomes for extracorporeal membrane oxygenation (ECMO), a rescue modality for patients with respiratory or cardiac failure, may vary by safety net status. We hypothesized SNH to be associated with inferior outcomes and costs of ECMO in a national cohort. Materials and Methods: The 2008-2017 National Inpatient Sample was queried for ECMO hospitalizations and safety net hospitals were identified. Multivariable regression was used to perform risk-adjusted comparisons of mortality, complications and resource utilization at safety net and non-safety net hospitals. Results: Of 36, 491 ECMO hospitalizations, 28.2% were at SNH. On adjusted comparison SNH was associated with increased odds of mortality (AOR: 1.23), tracheostomy use (AOR: 1.51), intracranial hemorrhage (AOR: 1.39), as well as infectious complications (AOR: 1.21, all P < .05), with NSNH as reference. SNH was also associated with increased hospitalization duration (β=+4.5 days) and hospitalization costs (β=+$32, 880, all P < .01). Conclusions: We have found SNH to be associated with inferior survival, increased complications, and higher costs compared to NSNH. These disparate outcomes warrant further studies examining systemic and hospital-level factors that may impact outcomes and resource use of ECMO at SNH.